2017
DOI: 10.1097/aud.0000000000000473
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hearing Aid Technology on Outcomes in Daily Life III: Localization

Abstract: Objective Compared to basic-feature hearing aids, premium-feature hearing aids have more advanced technologies and sophisticated features. The objective of this study was to explore the difference between premium-feature and basic-feature hearing aids in horizontal sound localization in both laboratory and daily life environments. We hypothesized that premium-feature hearing aids would yield better localization performance than basic-feature hearing aids. Design Exemplars of premium-feature and basic-feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 33 publications
2
24
0
5
Order By: Relevance
“…Contrary to laboratory tests, retrospective self-reports did not demonstrate any differential effect of premium DM/NR features compared with basic features across all outcome domains ( Figure 5). Furthermore, consistent with the research by Cox and her colleagues (Cox et al 2014(Cox et al , 2016Johnson et al 2016Johnson et al , 2017, premium HAs and basic HAs yielded similar real-world outcomes. Retrospective self-reports, however, did indicate that DM/NR features significantly improved speech understanding (by 0.33 points, or 3.3%, for premium HAs) and satisfaction (by 4.4% and 4.2% for premium and basic HAs, respectively), although the small amount of improvement might not be clinically important.…”
Section: Retrospective Self-reportssupporting
confidence: 83%
See 1 more Smart Citation
“…Contrary to laboratory tests, retrospective self-reports did not demonstrate any differential effect of premium DM/NR features compared with basic features across all outcome domains ( Figure 5). Furthermore, consistent with the research by Cox and her colleagues (Cox et al 2014(Cox et al , 2016Johnson et al 2016Johnson et al , 2017, premium HAs and basic HAs yielded similar real-world outcomes. Retrospective self-reports, however, did indicate that DM/NR features significantly improved speech understanding (by 0.33 points, or 3.3%, for premium HAs) and satisfaction (by 4.4% and 4.2% for premium and basic HAs, respectively), although the small amount of improvement might not be clinically important.…”
Section: Retrospective Self-reportssupporting
confidence: 83%
“…In contrast, evidence supporting the effect of premium DM/NR features in the real world is limited. Recently Cox and her colleagues conducted a clinical trial to examine the relative effect of premium-feature HAs compared with basicfeature HAs in improving speech understanding, listening effort, sound localization, and quality of life (Cox et al 2014(Cox et al , 2016Johnson et al 2016Johnson et al , 2017. Results indicated that there were no statistically significant or clinically important differences in improvement between premium and basic HAs in most laboratory tests and in the real world.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson and colleagues 11 found that only 10 studies were available in the peer-reviewed literature that had reported HA outcomes for patients with MSNHL, and most of those investigations only involved low levels of evidence, were rather dated, and reported findings for analog and early digital devices. Cox et al and Johnson et al, [21][22][23] however, reported outcomes from studies that compared entry-to premium-level ADT HAs for patients with mild and moderate SNHL. Although the findings for persons with MSNHL were similar to those with moderate losses, outcomes were not reported separately for the group with MSNHL.…”
Section: Abstract: Mild Hearing Loss Adults Advanced Digital Hearinmentioning
confidence: 99%
“…16,17 It is also the expected scenario for use of this technique in a clinical context. [25][26][27][28] For these reasons, free head movement was deemed to be an acceptable experimental choice in the present study.…”
Section: Localization Taskmentioning
confidence: 99%